Effects of Pleuran (Β–Glucan from Pleurotus Ostreatus) Supplementation on Incidence and Duration of COPD Exacerbations - Jordan Minov; Jovanka Bislimovska-Karadzhinska; Tatjana Petrova; Kristin Vasilevska; Sasho Stoleski; Dragan Mijakoski (ID Design Press/Scientific Foundation SPIROSKI, 2017)
BACKGROUND: 1,3/1,6-β–glucans are recognised as immunomodulators in human and veterinary medicine for over 50 years. AIM: To assess the effects of pleuran (1,3/1,6-β–glucan from Pleurotus ostreatus) on incidence and duration of bacterial exacerbations in patients with COPD. METHODS: We performed an observational, non-randomized, open-label study including 32 COPD patients (Group D) in whom besides the recommended chronic treatment for the stable disease were administered supplement combination containing pleuran 100 mg, vitamin C 60 mg and zinc 5 mg once daily over a three month-period (Group 1). Also, an equal number of Group D COPD patients who besides the recommended treatment for stable disease received the supplement combination containing vitamin C 60 mg and zinc 5 mg once daily, matched to the study subjects of the Group 1 by sex and age served as control (Group 2). RESULTS: Over the study period 57 exacerbations (24 in the Group 1 and 33 in the Group 2) were documented. A mean number of exacerbations over the study period was significantly lower in the Group1 (0.7 ± 0.4) as compared to their mean number in the Group 2 (1.0 ± 0.6) (P = 0.0218). Furthermore, a mean duration of exacerbations expressed in days needed for cure or clinical improvement (i.e. complete resolution of symptoms or return of the symptoms to their baseline severity) in the Group 1 (6.7 ± 0.8 days) was significantly shorter than the mean duration of exacerbations in the Group 2 (7.4 ± 1.3 days) (P = 0.0118). There was not reported any adverse effect during the study period by study subjects from both examined groups. CONCLUSION: Our findings indicated that pleuran might impact the incidence and duration of bacterial exacerbations in patients with COPD. There is a need for further studies for more precise determination of the influence of pleuran on the course of COPD.
Keywords: Chronic obstructive pulmonary disease; Exacerbations; Beta glucans; Pleuran; Supplement